2018
DOI: 10.12965/jer.1836110.055
|View full text |Cite
|
Sign up to set email alerts
|

The difference effect of estrogen on muscle tone of medial and lateral thigh muscle during ovulation

Abstract: The purpose of this study was to investigate the difference effect of estrogen on muscle tone of medial and lateral thigh muscle during ovulation (OV). Twenty-eight untrained eumenorrheic healthy women tested muscle stiffness and frequency of vastus medialis, vastus lateralis, semitendinosus, and biceps femoris during menstrual cycle (MC). MC were divided into menses (MS), OV, and luteal phase (LP). The muscle frequency of vastus medialis and semitendinosus were significant higher in OV (13.83±1.58 Hz, 15.62±2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 27 publications
(29 reference statements)
0
19
0
Order By: Relevance
“…The ankle has more laxness at ovulation compared to other periods of the menstrual cycle [15,16]. In another study on women during the menstrual cycle, changes in mechanical properties of the ankle muscles such as tone, stiffness, and elasticity were correlated to postural sway [11,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The ankle has more laxness at ovulation compared to other periods of the menstrual cycle [15,16]. In another study on women during the menstrual cycle, changes in mechanical properties of the ankle muscles such as tone, stiffness, and elasticity were correlated to postural sway [11,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…They revealed that hamstring stiffness did not change across the menstrual cycle; however, hamstring extensibility increased in ovulation phase. Moreover, Sung and Kim (12) reported that muscle tone and stiffness of the vastus medialis and semitendinosus muscles were higher in ovulation phase compared to follicular and luteal phases; however, menstrual cycle did not affect the muscle tone and stiffness of the vastus lateralis and biceps femoris muscles. Lee at al.…”
Section: Discussionmentioning
confidence: 97%
“…The sample size calculation was performed using the SPSS Sample Power 3.0 software (IBM Corporation, Armonk, NY). It was estimated that at least 21 females had to be included in this study for 80% power with 5% type-1 error level to detect a minimum significant difference of 35 N • m for muscle stiffness among menstrual phases, when the average value of muscle stiffness in follicular phase is 242 N • m, with a standard deviation of 35 N • m (12).…”
Section: Sample Size Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscle and tendon stiffness have been investigated in a number of studies to establish whether MC phase is a risk factor for soft tissue injuries; some studies concluded that stiffness is affected by MC phase [ 30 , 31 ]. A relationship has been considered between stiffness of lower limb muscles and tendons and performance in tests that require reactive hops or jumps, such as short sprints or multiple jump tests [ 32 , 33 ], as greater stiffness provides for better storage and use of elastic energy [ 32 ]; MC phase could also alter performance via changes in tissue stiffness.…”
Section: Introductionmentioning
confidence: 99%